PROXIMATE ANALYSIS OF NIGERIAN CROTON GRATISSIMUS, CROTON LOBATUS, CROTON MEMBRANACEUS AND CROTON PENDULIFLORUS (FUDMA JOURNAL OF SCIENCES, 2024)
With about 1300 species of herbs, shrubs, trees, and lianas, Croton (Euphorbiaceae) is one of the largest genera of flowering plants. It is an important component of secondary vegetation in the tropics and subtropics of the world and has ecological significance. The growing consumer interest in ingredients originating from natural sources has led to a recent surge in the demand for natural extracts in the food, cosmetics, and pharmaceutical industries. Determining the proximate analysis of Croton gratissimus, lobatus, memebranaceus, and penduliflorus stembarks is the aim of this work. The proximate analysis was carried out using AOAC standard procedures in order to assess the moisture contents, dry matters, crude proteins, ash contents, carbohydrates, fat contents and fiber contents of the stated plant materials. The findings showed that there was a significant amount of dry matter, fiber and carbohydrates at 82.52%, 32.48% and 38.63% respectively in the stem bark of Croton gratissimus. Croton lobatus showed the highest amount of protein and fat content at 17.83% and 4.71% respectively while Croton lobatus and penduliflorus contains the same amount of moisture at 24.53%. Findings of the study showed that the stembarks of the plants possess high nutritional value.
Keywords: Ethnomedicinal uses; Proximate analysis; Croton; Croton gratissimus; Croton lobatus; Croton membranaceus; Croton penduliflorus